O processo argumentativo de alunos do nono ano do Ensino Fundamental envolvendo situações sobre a eletrização - Jango, Aline Agnelo [UNESP] (2015)
This research, of qualitative nature, aimed to investigate how ninth grade students provide explanations related to the electrification processes using interactive activities, aiming to answer the components present in the arguments. The participants in the work were a middle shool teacher, also the researcher, and four ninth grade students from a private school in the state of São Paulo. Six problems were proposed: two about electrification by friction; two about electrification by contact and two about induction and polarization, all done by the students in this order. The application of these activities occurred in three steps. First, a larger problem of shock was presented, followed by a time for the students to individually record results about the solution for and explanation of the issues. The second step was the application of the six activities, always starting from the individual results about the hypothesis creating a solution for each problem, followed by the validation or invalidation of the hypothesis, as well as rewriting the exploratory model. The third and final stage restated the larger problem in order to verify whether or not any changes needed to be made in the first explanation provided by the students. Data analysis was prepared three times. The first time was related to the larger problem. The second time was particularly related to the six problems introduced to the students about electrification. The third time dealt with restating the larger problem after the completing the six activities. The data analyzed showed that these types of activities allow students to being making connections related to electrification also valid for future classes, where the teacher will conceptually deal with the topic and use the results of the activities to prepare classes that break down the confusion that was apparent during the practice. The data also showed the relation between student involvement in the activities and their...